The vagabonds : the story of Henry Ford and Thomas Edison's ten-year road trip - Guinn, Jeff (Simon & Schuster nonfiction original hardcover, 2019)
"A brilliant portrait of two American giants, Thomas Edison and Henry Ford, and America entering the automobile age, told through the fascinating but little-known narrative of the summer road trips taken by Edison and Ford"--